Pap smear in antenatal women: a valuable opportunity for screening and awareness - Ahuja, Rashmi; Sharma, Priyanka; Chawla, Raina (International Journal of Research in Medical Sciences, 2020)
Background: Pregnancy creates an important opportunity to screen the cervix for neoplastic and infectious diseases and to spread awareness. A pap smear is simple, cost effective and safe in pregnancy. In low resource countries, this may be the only opportunity when the woman visits a health centre. It also helps identify and treat infections that could hamper the pregnancy outcome. Objective of the study is to determine the awareness of pap smear as a cervical cancer screening test in antenatal women; to determine the incidence of cervical neoplasia and premalignant lesions of the cervix in antenatal women. Methods: A cross-sectional study was carried out between November 2018 to April 2019. Inclusion criteria were pregnant women in the first trimester. Exclusion criteria were pregnancy greater than 12 weeks, symptoms of vaginal infection, history of sexual intercourse or vaginal medication or bleeding in the last 48 hours or a normal pap smear in the last 3 years. The reporting was done as per Bethesda 2014. Results: 308 women underwent a pap smear in their 1st trimester. 94% were satisfactory smears and 3(0.9%) an abnormal smear (2 LSIL and 1 ASCUS). 31.2% had inflammatory smears. Only 15 women were aware of pap smear as a test for cancer cervix screening and all these women were graduates and above. No women had ever had a pap smear test in the past. One fifth of women studied had 1 or more risk factor the commonest being early age at first intercourse. Conclusions: The antenatal period should be utilized as an opportunity to screen women for cancer cervix.